The pursuit of college for all: Ends and means in 'no excuses' charter schools. (July 2017) - Lamboy, Lily; Lu, Amanda
In recent years, 'No Excuses' charter schools have been hailed as a promising solution to closing the 'achievement gap' between low-income students of color and their high-income White peers. These schools, which have the explicit goal of college completion for all, measure success in terms of standardized test performance and college acceptance rates. Schools use rigid instructional and disciplinary practices to achieve success along these dimensions. And they are broadly successful, boasting test scores and college acceptance rates that are higher than average for the students they serve. For this reason, No Excuses schools are proliferating rapidly, dominating the educational landscape in low-income minority-serving urban districts. In this article, we argue that a focus on these standardized test performance and college acceptance drives schools to participate in practices that may impede other essential aspects of student learning and development. We outline a research agenda for social scientists, philosophers, and policymakers interested in evaluating the holistic success of these schools. We focus on four key components: the goal of college-for-all itself and its effects on student outcomes, instructional practices geared toward success on standardized exams, disciplinary practices that demand rigid physical and psychological conformity and punish minor infractions, and teacher practices that traumatize students and/or fail to meet the needs of students who encounter significant trauma in their homes and neighborhoods. We conclude that more information is needed before reformers can embrace No Excuses schools as a mechanism for eradicating inequality and promoting educational and psychosocial growth for students in poor communities of color. This research agenda is urgent as No Excuses charter networks are growing rapidly, and we urge policymakers and social scientists to take this task seriously before continuing to charter these schools wholesale.